Potentials and challenges of next generation sequencing-guided individualized treatment for management of rifampicin-resistant tuberculosis – A qualitative study - Tu Pham Hien Trang; Antonio Barrenechea-Pulache; Katinka De Wet; Boitumelo Fanampe; Salome Charalambous; Annelies Van Rie (PLoS ONE, 2026)
Background Next generation sequencing (NGS) is a powerful technology for diagnosing and managing rifampicin-resistant tuberculosis (RR-TB). To facilitate its integration into routine RR-TB care, a treatment recommendation system was developed to automatically translate whole genome sequencing (WGS) results into treatment recommendations. The effectiveness of WGS-guided treatment recommendations was evaluated in the SMARTT trial. Methods We conducted a focus group discussion among eleven health care workers (HCWs) involved with managing SMARTT trial participants to explore their experiences and attitudes towards WGS-guided treatment recommendations. Thematic analysis was undertaken with an inductive approach. Results The use of WGS and automated treatment recommendations simplified drug susceptibility testing (DST) and was perceived as beneficial to patients and HCWs. The strategy did not negatively impact HCWs autonomy and competence. Trust and acceptance were compromised by slow turn-around time, guideline deviations, discordance between DST methods, and unfavorable outcomes of some patients. Implementation challenges included drug stock-out, limited internet connection and training requirements. Conclusion NGS accompanied by automated treatment recommendations holds promise for improving RR-TB care in high-burden settings, benefiting both patients and HCWs. Perspectives of policymakers, laboratory staff and patients should be explored to support the routine implementation of NGS in RR-TB management.